Queues with Working Vacations: A Survey - Dieter Fiems (Mathematics)
In this paper, we present an extensive literature review on queueing systems with working vacations. The concept of a working vacation generalises the concept of server vacations, which are time periods during which the server is absent and cannot serve waiting customers. During a working vacation, the server remains active, albeit at a reduced service rate. Our literature survey mainly highlights the structural properties of the Markov chains that underlie working vacation queueing models, as well as various methodological approaches to assessing the performance of queues with working vacations. Moreover, queueing games with working vacations and applications of queues with working vacations are discussed.